2010
DOI: 10.3390/s101110467
|View full text |Cite
|
Sign up to set email alerts
|

A Local Weighted Nearest Neighbor Algorithm and a Weighted and Constrained Least-Squared Method for Mixed Odor Analysis by Electronic Nose Systems

Abstract: A great deal of work has been done to develop techniques for odor analysis by electronic nose systems. These analyses mostly focus on identifying a particular odor by comparing with a known odor dataset. However, in many situations, it would be more practical if each individual odorant could be determined directly. This paper proposes two methods for such odor components analysis for electronic nose systems. First, a K-nearest neighbor (KNN)-based local weighted nearest neighbor (LWNN) algorithm is proposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…47,48 Data analysis Data analysis and classication were performed using standard k-nearest neighbor (kNN) machine learning algorithms via a program code written in Python. 50,53 For the kNN classication, a total of 100 data points were collected before the end of the vapor exposure period, this means when the equilibrium is (essentially) reached. With the sampling rate of the device, this corresponds to a time period of approximately 2.5 min (i.e.…”
Section: Sensor Arraymentioning
confidence: 99%
“…47,48 Data analysis Data analysis and classication were performed using standard k-nearest neighbor (kNN) machine learning algorithms via a program code written in Python. 50,53 For the kNN classication, a total of 100 data points were collected before the end of the vapor exposure period, this means when the equilibrium is (essentially) reached. With the sampling rate of the device, this corresponds to a time period of approximately 2.5 min (i.e.…”
Section: Sensor Arraymentioning
confidence: 99%
“…Numerous other approaches have been reported that implemented a pattern-matching method for the identification and classification of odours [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Collectively, these studies indicate that the pattern-recognition engine forms an essential part of the existing electronic nose systems.…”
Section: Conventional E-nose Systemsmentioning
confidence: 99%
“…The microprocessor embeds a k-nearest neighbor (KNN) classification algorithm for simplicity to achieve a good efficiency and performance (Tang et al, 2010). Fig.…”
Section: The Portable E-nose Systemmentioning
confidence: 99%